2021
DOI: 10.3390/su132313450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Green Innovation Efficiency on Carbon Emission Reduction in the Guangdong-Hong Kong-Macao GBA

Abstract: Climate change has become a global issue of general concern to human society. It is not only an environmental issue, but also a development issue. As the second largest economy in the world, China has adhered to its commitments in the Paris Agreement and formulated a series of autonomous action targets. In this context, scholars have done a lot of research focusing on carbon emission reduction, but have neglected the spatial correlation of carbon emission, and lack of research on carbon emission reduction in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…High-level human capital promotes green innovation [ 59 ]. Green innovation ( GI N ) will largely affect carbon emissions [ 61 ], affecting green economic development [ 63 ]. In this paper, green innovation is measured by the number of green invention patent applications in prefecture level cities.…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…High-level human capital promotes green innovation [ 59 ]. Green innovation ( GI N ) will largely affect carbon emissions [ 61 ], affecting green economic development [ 63 ]. In this paper, green innovation is measured by the number of green invention patent applications in prefecture level cities.…”
Section: Methodology and Datamentioning
confidence: 99%
“…However, existing studies have shown that the relationship between green innovation and GEE is often nonlinear. Chen and Huo [ 61 ] and Shi et al [ 62 ] argue that there is an inverted U-shaped relationship between innovation and carbon emissions. Hu et al [ 63 ] finds that there is a U-shaped relationship between green innovation and green development.…”
Section: Literature Review and Hypothesis Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot cities can use their advantages in green innovation technology and governance experience to drive the joint upgrading of related industries and share management experience with adjacent regions. Regions with large-scale high-carbon industries can learn from the development experience of pilot cities, improve their industrial technology innovation [38], optimize the structure of high-carbon industries, and move forward from traditional to high-end industries. At the same time, a regional carbon emission reduction cooperation mechanism can be established to achieve effective interregional docking in energy policies such as new energy technology R&D and energy conservation subsidies and promote the sharing of resources and low-carbon technologies among provinces.…”
Section: Study Conclusion and Recommendationsmentioning
confidence: 99%
“…The innovative behavior of enterprises is considered to be an important way to solve environmental pollution and cope with climate change (Lin et al, 2021), which can increase the proportion of clean energy use while reducing the waste of resources (Feng et al, 2021;Dong et al, 2022;Lin and Ma, 2022). In addition, enterprises can also improve the effect of EG by means of green transformation (Zhu et al, 2021) and improving the efficiency of total factor productivity Chen and Huo, 2021).…”
Section: Study On the Impact Of Enterprise On Egmentioning
confidence: 99%